IMPROVING STUDENTS’ READING SKILLS THROUGH PUNCTUATIONS BY USING GOOGLE CLASSROOM APPLICATION AT GRADE XII MS 1 OF SMA NEGERI PLUS PROVINSI RIAU - Tengku Emadesti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this research was to explain whether punctuations could better improve the students’ reading skill through Google Classroom application at grade XII MS 1 of SMA Negeri Plus Provinsi Riau and to explain what factors influenced it. The data were collected by using observation checklists, field notes, and tests. Then, qualitative data were analyzed by data managing, reading or memoing, describing, classifying, and interpreting. Meanwhile, quantitative data were analyzed through the percentage (scores of reading test by using Google Classroom), matrix, and graph. This classroom action research consisted of two cycles constituting three meetings for each cycle. The result of this research showed that implementing Google Classroom improved the students’ reading skill in each cycle. It was found that at the end of the first cycle, the percentage of the students’ reading skill was 83.20%. However, this result was still unsatisfied. At the end of the second cycle, the improvement of the students’ reading skills after implementing Google Classroom was 90.40%. It implied that there was an improvement of the students’ reading skill through punctuations through the implementation of Google Classroom at the end of the second cycle. In conclusion, the use of punctuations improved the students’ reading skills through Google Classroom application.